The Virtual People Set: Developing Computer-Generated Stimuli for the Assessment of Pedophilic Sexual Interest. (December 2013) - Dombert, Beate; Mokros, Andreas; Brückner, Eva; Schlegl, Verena; Antfolk, Jan; Bäckström, Anna; Zappalà, Angelo; Osterheider, Michael; Santtila, Pekka
The implicit assessment of pedophilic sexual interest through viewing-time methods necessitates visual stimuli. There are grave ethical and legal concerns against using pictures of real children, however. The present report is a summary of findings on a new set of 108 computer-generated stimuli. The images vary in terms of gender (female/male), explicitness (naked/clothed), and physical maturity (prepubescent, pubescent, and adult) of the persons depicted. A series of three studies tested the internal and external validity of the picture set. Studies 1 and 2 yielded good-to-high estimates of observer agreement with regard to stimulus maturity levels by two methods (categorization and paired comparison). Study 3 extended these findings with regard to judgments made by convicted child sexual offenders.